Cognitive Effects of Lacosamide in Patients with Drug Refractory Focal Epilepsy: A Prospective Observational Study - Modi, MD, Dr. Sophia B; S, MD, Dr. Asha; Iype, MD, MRCP(UK), FRCP(Edin), DM, Dr. Thomas; Kanakamma, MD, Dr. Libu Gnanaseelan; Rajan, Neuropsychologist, Mrs. Reeja (International Journal of Innovative Research in Medical Science, 2021)
Objectives: This study was conducted to obtain data on the cognitive effects of lacosamide in Indian population. Methodology: An open labelled prospective observational study in 22 patients who suffered from focal epilepsy. Results: All the pre and post lacosamide cognition scores showed statistically significant positive correlation in this study. Average initial seizure frequency per month was 3.56 (SD 2.58) and median frequency 2.5 seizures per month. Range being 1-8 per month. At the final follow-up at 6months, 87.5% of the study subjects had no seizures. In the remaining12.5% of patients, reduction in seizure frequency was observed. The difference in frequency is statistically significant (Wilcoxon Signed Ranks TestP <0.001). Conclusion: Excellent seizure control is observed in patients with refractory focal epilepsy treated with lacosamide. Also, lacosamide has no serious adverse effects or drug interactions. In this study, it is observed that unlike many AEDs, lacosamide contributed to significant improvement in cognition.